The impact of chronic obstructive pulmonary disease on bone strength - Tsukamoto, Manabu; Nabeshima, Takayuki; Wang, Ke-Yong; Mano, Yosuke; Arakawa, Daisuke; Okada, Yasuaki; Yamanaka, Yoshiaki; Okimoto, Nobukazu; Sakai, Akinori (Journal of bone and mineral metabolism, 2024)
Chronic obstructive pulmonary disease (COPD) is a lifestyle-related disease that develops in middle-aged and older adults, often due to smoking habits, and has been noted to cause bone fragility. COPD is a risk factor for osteoporosis and fragility fracture, and a high prevalence of osteoporosis and incidence of vertebral fractures have been shown in patients with COPD. Findings of lung tissue analysis in patients with COPD are primarily emphysema with a loss of alveolar septal walls, and the severity of pulmonary emphysema is negatively correlated with thoracic spine bone mineral density (BMD). On the other hand, epidemiological studies on COPD and fracture risk have reported a BMD-independent increase in fracture risk; however, verification in animal models and human bone biopsy samples has been slow, and the essential pathogenesis has not been elucidated. The detailed pathological/molecular mechanisms of musculoskeletal complications in patients with COPD are unknown, and basic research is needed to elucidate the mechanisms. This paper discusses the impacts of COPD on bone strength, focusing on findings in animal models in terms of bone microstructure, bone metabolic dynamics, and material properties.